2016
DOI: 10.25215/0304.066
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Adjustment of Sports persons

Abstract: The demand for adjustment is universal to all human beings and characterized by uniqueness, dynamicity, pervasiveness and indispensability. The processes and mechanisms of adjustment entail factors associated with the personal attributes of the individuals, socio-cultural milieu and genetic endowment which determine its exact nature, extent and quality. The sports relationship is unique and places a different type of demand on the part of sportspersons. Out of many stake holders of adjustment in the field of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The relationship between emotional intelligence and self-adjustment is supported by Adeyemo's research (2009) which shows that there is a significant relationship between emotional intelligence and selfadjustment, in which high emotional intelligence translates into a high average value in self-adjustment. The research by Singh and Bhardwaj (2016) shows that there is a relationship between emotional intelligence and adjustment, by clarifying that emotional intelligence is very important in determining sportsman's adjustment. Furthermore, according to research by Amin, Patel, and Sivastava (2016), it shows that there is a relationship between emotional intelligence and adjustment in adolescents, but there is no significant difference between female and male adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between emotional intelligence and self-adjustment is supported by Adeyemo's research (2009) which shows that there is a significant relationship between emotional intelligence and selfadjustment, in which high emotional intelligence translates into a high average value in self-adjustment. The research by Singh and Bhardwaj (2016) shows that there is a relationship between emotional intelligence and adjustment, by clarifying that emotional intelligence is very important in determining sportsman's adjustment. Furthermore, according to research by Amin, Patel, and Sivastava (2016), it shows that there is a relationship between emotional intelligence and adjustment in adolescents, but there is no significant difference between female and male adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional intelligence is defined as "the extent to which a person processes emotional information adequately" (Mayer et al, 2000(Mayer et al, , 2016. Ample evidence showed that emotional intelligence is associated with classic indicators of mental health significantly (e.g., Cejudo, 2016;Singh and Bhardwaj, 2016). For example, Lea et al (2019) used metaanalyses method to investigate the relationships between emotional intelligence and mental health, and found that higher emotional intelligence is associated with lower levels of depression, anxiety, and psychological distress and less likely to suicide (García-Sancho et al, 2014).…”
Section: Introductionmentioning
confidence: 99%